Genetic Inhibition of Plppr5 Aggravates Hypoxic-Ischemie-Induced Cortical Damage and Excitotoxic Phenotype - Sun, Yuxiao; Jin, Mei-fang; Li, Lili; Liu, Yueying; Wang, Dandan; Ni, Hong (Frontiers in Neuroscience, 2022)
Hypoxic ischemia (HI) is the most common acute brain threat in newborns and the main cause of neurodevelopmental handicaps. However, clinical interventions are still very limited and have side effects. Lipid phosphophosphatase-related proteins (PLPPRs) are regulators of mitochondrial membrane integrity and energy metabolism. We recently showed that plppr5 knockout aggravated HI damage and partially weakened the neuroprotection of melatonin in some aspects, which suggests that mitochondrial homeostasis mediated by plppr5 may be a new intervention target for HI. This study was undertaken to determine the long-term effects of Pllppr5 gene knockout on HI brain injury, focusing on the neuronal excitatory phenotypes, and to determine the effects of Pllppr5 gene silencing on neuronal zinc metabolism and mitochondrial function in vitro. Plppr5-deficient (Plppr5(-/-)) and wild-type (WT) 10-day old mice were subjected to hypoxia-ischemia. Lesion volumes and neuroexcitotoxic phenotypes were quantified together with ZnT1 protein expression in hippocampus. In addition, hippocampal HT22 neuronal cultures were exposed to oxygen and glucose deprivation/reoxygenation, with or without Plppr5 interference. Mitochondrial oxidative stress indicator ROS, mitochondrial ZnT1 protein expression and zinc ion content were detected. Results: Plppr5-deficient mice subjected to hypoxia-ischemia at postnatal day 10 present significantly higher cerebral infarction. Pllppr5(-/-) mice were endowed with a more pronounced superexcitability phenotype at 4 weeks after HI, manifested as a reduced seizure threshold. ZnT1 protein was also found reduced in Plppr5-deficient mice as well as in mice subjected to excitotoxicity. Plppr5 knockout in vivo aggravated the hypoxic-ischemic brain damage phenotype, including infarct volume and seizure threshold. Besides, knockout of the Plppr5 gene reduced the MFS scores to a certain extent. In vitro Plppr5 silencing directly interferes with the homeostasis of neuronal zinc and mitochondrial metabolism, and exacerbates hypoxia-induced mitochondrial oxidative stress damage. In summary, our findings demonstrate for the first time that PLPPR5-deficient mouse pups exposed to neuronal hypoxia and ischemia exhibited aggravated acute brain injury and long-term brain excitability compared with the same treated WT pups, which involves zinc and mitochondrial-dependent metabolic pathways in the hippocampus. These data support further investigation into novel approaches to target trace element zinc-related mitochondrial homeostasis in neonatal HIE.